AYURVEDIC APPROACH TOWARDS GRDHRASI AND STHOULYA –A CASE STUDY - Wilson, *Nicy; MJ, Prashasth; Dr, Muralidhara (International Journal of Ayurveda and Pharma Research, 2017)
Low back pain is major cause of morbidity throughout the world. There is only conservative treatment giving short term relief in pain or surgical intervention with side effect. But these are not successful and therefore those who are suffering from this are always in search of result oriented remedy. Management of such diseases in an obese patient is still challenging. Here in this case study a 49 year old female patient presented with the complaints of Low back pain radiating to both the lower limbs posteriorly till the toes and with weight of 88 kg and height is 148 cms. This was diagnosed as Grdhrasi and Sthoulya. Hence the line of treatment adopted was Kapha-medohara and Vata shamana which included both Rukshana and Brhmana chikitsa along with Shamanoushadhis. The patient recovered remarkably and was able to do her routine activities without any pain.